2017
DOI: 10.1027/1864-9335/a000308
|View full text |Cite
|
Sign up to set email alerts
|

The Ego Could Be Depleted, Providing Initial Exertion Is Depleting

Abstract: Abstract. The ego depletion effect has been examined by over 300 independent studies during the past two decades. Despite its pervasive influence, recently this effect has been severely challenged and asserted to be a fake. Based on an up-to-date meta-analysis that examined the effectiveness of each frequently used depleting task, we preregistered the current experiment with the aim to examine whether there would be an ego depletion effect when the Stroop task is used as the depleting task. The results demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 14 publications
2
37
0
Order By: Relevance
“…Hypothesis awareness . Introducing Perceived Awareness of Research Hypothesis scores as covariates did not change significantly our estimates as well as removing participants above 3 standard deviations on the Perceived Awareness of Research Hypothesis scores .…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Hypothesis awareness . Introducing Perceived Awareness of Research Hypothesis scores as covariates did not change significantly our estimates as well as removing participants above 3 standard deviations on the Perceived Awareness of Research Hypothesis scores .…”
Section: Resultsmentioning
confidence: 65%
“…An ego‐depletion task typically consists in reducing volitional processing at time 2 (here, exposure to sponsorship) by asking the participant to perform a cognitively demanding task at time 1 . Recent conceptualisation has shown that impairing self‐control tends to also reduce executive and cognitive control in a broader sense, which is particularly efficient on tasks requiring motivation to engage in a task requiring some amount of mental effort . Furthermore, impairing self‐regulation is close to what an individual might experience as external pressures in daily life situations, in which one is more likely to have limited resources to and be targeted by multiple external demanding tasks that hinder self‐control.…”
Section: Hypothesesmentioning
confidence: 99%
“…For consistency with this decision, I also included the study by Sripada, Kessler, and Jonides (2014), on which the registered replication report was based, and a recent study by Emmerling et al (2017) that relied on the same outcome task. Following the recommendations of the reviewers of an earlier draft of this article, I also included in the updated analyses two pre-registered studies by Dang, Liu, Liu, and Mao (2017) and Ego depletion may disappear by 2020 9 Garrison, Finley, and Schmeichel (in press), although some of the studies reported in these papers do not comply with the selection criteria of Carter et al Carter et al (2015) and Dang (2018)…”
Section: Updated Literature Search and Computation Of Effect Sizesmentioning
confidence: 99%
“…Similarly, studies that employed other depleting tasks also yielded results from which no definitive conclusion could be drawn, with some studies reporting substantive, non-zero effects (Bayer & Osher, 2018;Dang, Liu, Liu, & Mao, 2017;Garrison, Finley, & Schmeichel, 2019) while others reporting effects that were no different from zero (Etherton, Osborne, Stephenson, Grace, Jones, & De Nadai, 2018;Lurquin et al, 2016;Singh & Göritz, 2018).…”
Section: Addressing Replication Issuesmentioning
confidence: 99%